Olive Oil as Lubricant in Massage for Overcoming Decubitus in Patients with Intra Cerebral Hemorrhage - Ridla, Akhmad Zainur; Cahyani, Nurul Izzah Regita; Setioputro, Baskoro; Wahyudi, Agus Setyo (Jurnal Kesehatan Komunitas Indonesia, 2023)
Intra Cerebral hemorrhage is a complication of stroke disease. The typical symptoms in ICH patients are a loss of consciousness and getting long treatment at home. As a result, the patient will lack mobilization and experience muscle stiffness which can aggravate the patient's condition; it will also slow down the patient's healing process and increase the risk of decubitus. This study aimed to determine the effectiveness of giving a massage with olive oil to overcome. This study used a case report that described the case of ICH patients with skin and tissue integrity disorders problems given the intervention of massage with olive oil carried out for five days of treatment and carried out one time a day with a duration of 10-20 minutes. The Braden scale was used to measure the level of decubitus consisting of 6 question indicator items. This study found an increase in score on the first day with a score of 11 and on the fifth-day score of 14 with an increase from a severe risk of decubitus to a moderate risk of decubitus in patients. This procedure has proven useful for reducing decubitus in hospital patients with prolonged bed rest.